Crack Resistance of Encentrally Compressed Reinforced Concrete Elements in Natural Conditions of the Republic of Uzbekistan - Rizaev, B. Sh.; Akhmedov, PhD, I. G; Umarov, I. I. (Journal of Higher Education and Academic Advancement, 2024)
This article is devoted to the theoretical and experimental study of the crack resistance of eccentrically compressed reinforced concrete elements under dry, hot climate conditions. Methods for conducting experimental research have been developed and the nature of the increase in the deformative properties of heavy concrete under dry, hot climate conditions has been studied. Based on the research conducted, it has been established that in conditions of a dry, hot climate, the deformative properties of concrete change due to the action of temperature and humidity, which must be taken into account in the calculations.